2007
DOI: 10.1007/s00270-005-0342-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Uterine Artery Embolization (PUAE) Before Uterine Fibroid Myomectomy

Abstract: Preoperative embolization is associated with minimal intraoperative blood loss. It does not increase the complication rate or impair operative dissection, and improves the chances of performing conservative surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 34 publications
2
31
0
1
Order By: Relevance
“…Because the material is absorbed completely, the vascular lumen and blood flow are fully restored after a few weeks. Gelatine sponge is used before surgery to decrease bleeding during the procedure, most notably when treating patients with tumours [4].…”
Section: A Absorbable Sterile Gelatine Sponge Particlesmentioning
confidence: 99%
“…Because the material is absorbed completely, the vascular lumen and blood flow are fully restored after a few weeks. Gelatine sponge is used before surgery to decrease bleeding during the procedure, most notably when treating patients with tumours [4].…”
Section: A Absorbable Sterile Gelatine Sponge Particlesmentioning
confidence: 99%
“…Although clinical manifestations of uterine leiomyomata and uterine adenomyosis are similar, their treatment may differ. In addition to medical treatment and hysterectomy, uterine-sparing treatment options such as myomectomy, hysteroscopic resection, and uterine artery embolization (UAE) are well-established treatment options for symptomatic leiomyomata [8].…”
Section: Introductionmentioning
confidence: 99%
“…Very little information can be found in the literature on the use of UAE before myomectomy. Dumousset et al (21) reported 22 cases of preoperative UAE and concluded that this procedure does not increase the complication rate or impair operative dissection, and therefore improves the chances of performing conservative surgery. They claim that a multidisciplinary discussion led them to believe that excision of uterine fibroids in three patients would not have been possible without preliminary preoperative UAE, due to the presence of polymyomatous uteri with dominant fibroids larger than 8 cm.…”
Section: Discussionmentioning
confidence: 97%